THU0517 Invasive Fungal Infections Survey in 852 Childhood-Onset Systemic Lupus Erythematosus: A Multicenter Cohort. (9th June 2015) - Silva, M.F.; Ferriani, M.P.; Terreri, M.T.; Pereira, R.M.; Magalhães, C.S.; Bonfa, E.; Campos, L.M.; Okuda, E.M.; Appenzeller, S.; Ferriani, V.P.; Barbosa, C.M.; Ramos, V.C.; et al.
Abstract : Background: The majority of infections in childhood-onset systemic lupus erythematosus (cSLE) patients are caused by virus and bacteria, and less frequently by opportunistic agents, such as fungi. 1 However, studies evaluating solely invasive fungal infections (IFI) in cSLE patients are restricted to case reports or case series 1 without any systematic evaluation of the possible associated risk factors and outcomes in pediatric lupus population. Objectives: To study the prevalence, risk factors and mortality of IFI in cSLE patients. Methods: A retrospective multicenter cohort study was performed in 852 cSLE patients from 10 Pediatric Rheumatology services of São Paulo state, Brazil. An investigator meeting was held and all participants received database training. IFI were diagnosed according to EORTC/MSG Consensus Group (proven, probable and possible). 2 Demographic data, clinical, laboratorial, SLEDAI-2K, SLICC/ACR-DI, treatment and outcome were also evaluated. Results: IFI were recorded in 33/852 (3.9%) cSLE patients. Proven IFI was evidenced in 22 cSLE patients, probable IFI in 5 and possible IFI in 6. The most frequent types of IFI were candidiasis (n=20) and aspergillosis (n=9). The median of disease duration was lower (1.0 vs. 4.7 years, p<0.0001), with a higher current SLEDAI-2K [19.5 (0-44) vs. 2 (0-45), p<0.0001] and current prednisone dose [50 (10-60) vs. 10 (2-90) mg/day, p<0.0001] in patients with IFI compared to those without IFI. The frequency of death was higher in the former group (51% vs. 6%, p<0.0001). Logistic regression analysis revealed that SLEDAI-2K (OR=1.108; 95%CI=1.057-1.163; p<0.0001), current prednisone dose (OR=1.046; 95%CI=1.021-1.071; p<0.0001) and disease duration (OR=0.984; 95%CI=0.969-0.998; p=0.030) were independent risk factors for IFI (R 2 Nagelkerke 0.425). Conclusions: This was the first study that characterized IFI in a large cSLE population. We identified that disease activity and glucocorticoid use were the main risk factors for these life-threatening infections, mainly in early disease course and with a high rate of fatal outcome. References: Silva MF, Ribeiro AS, Fiorot FJ, et al. Invasive aspergillosis: a severe infection in juvenile systemic lupus erythematosus patients. Lupus 2012;21:1011-6. De Pauw B, Walsh TJ, Donnelly JP, et al. Revised definitions of invasive fungal disease from the European Organization for Research and Treatment of Cancer/Invasive Fungal Infections Cooperative Group and the National Institute of Allergy and Infectious Diseases Mycoses Study Group (EORTC/MSG) Consensus Group. Clin Infect Dis 2008;46:1813-21. Disclosure of Interest: None declared